Queer youth, Facebook and faith: Facebook methodologies and online identities. (November 2014) - Taylor, Yvette; Falconer, Emily; Snowdon, Ria
'Making space for queer-identifying religious youth' (2011–2013) is an Economic and Social Research Council (ESRC)-funded project, which seeks to shed light on youth cultures, queer community and religiosity. While non-heterosexuality is often associated with secularism, and some sources cast religion as automatically negative or harmful to the realisation of lesbian, gay, bisexual and transgender (LGBT) identity (or 'coming out'), we explore how queer Christian youth negotiate sexual–religious identities. There is a dearth of studies on queer religious youth, yet an emerging and continuing interest in the role of digital technologies for the identities of young people. Based on interviews with 38 LGBT, 'religious' young people, this article examines Facebook, as well as wider social networking sites and the online environment and communities. Engaging with the key concept of 'online embodiment', this article takes a closer analysis of embodiment, emotion and temporality to approach the role of Facebook in the lives of queer religious youth. Furthermore, it explores the methodological dilemmas evoked by the presence of Facebook in qualitative research with specific groups of young people.